EFEKTIVITAS PENGGUNAAN KAHOOT SEBAGAI MEDIA EVALUASI PEMBELAJARAN KELAS VII SMP - Rini Amalia; Muhammad Nawir; Nurindah (Almeera Education, 2022)
This study aims to determine the effectiveness of using kahoot as a medium for evaluating learning for class VII SMP Negeri Bajeng, Gowa Regency. Therefore, to achieve this goal the researchers used data collection techniques with observations and tests on the kehoot application with a population of 192 and a sample of 66 people. Then the data is processed using descriptive quantitative analysis to determine the effectiveness of the evaluation using the Kahoot application. The results of this study indicate that the effectiveness of using Kahoot as a medium for evaluating learning in English class VII subjects at SMP Negeri 3 Bajeng, Gowa Regency, namely based on the results of observations made using Kahoot in English subjects for class VII.A is in the very good category with a percentage of 100%, class VII.C is in the very good category with a percentage of 100% and VII.F is in a good category with a percentage of 80%. In the test results, students are in the good category with an average percentage score of 76.81%. From the results of this study, it can be concluded that the use of Kahoot as a medium for evaluating learning in English subjects in class VII SMP Negeri 3 Bajeng, Gowa Regency is effective based on the effective category.